ANALISIS STABILITAS LERENG MENGGUNAKAN BAMBOO CRIB WALL - Nirmala, Angelina Christi Agung; Prihatiningsih, Aniek (JMTS: Jurnal Mitra Teknik Sipil, 2026)
Slope stability is a critical aspect of geotechnical engineering, particularly on steep terrains prone to landslides. This study analyzes the effectiveness of Bamboo Crib Walls as an eco-friendly and economical reinforcement alternative by comparing single-trap and multi-trap (terraced) designs. Stability analysis was conducted using the Limit Equilibrium Method on a 14-meter high slope with a 60° inclination in Tambakmerang Village, Wonogiri. Simulation results showed the existing slope has a Safety Factor (SF) of 1.366. While categorized as relatively stable, it fails to meet the SNI 8460:2017 standard for permanent slopes with high uncertainty, which requires an SF ≥ 2.0. The single-trap design (H = 4 m, B = 3 m) increased the SF to 1.571, yet remained below the minimum national requirement. In contrast, the terraced design (2-trap) with identical dimensions achieved optimal stability with an SF of 2.823, significantly exceeding the safety standard. This study concludes that the terraced Bamboo Crib Wall is the most effective solution, as the terracing system provides superior load distribution and retention compared to the single-trap model in resisting driving forces on steep slopes. Abstrak Stabilitas lereng merupakan aspek krusial dalam rekayasa geoteknik, terutama pada topografi curam yang rentan terhadap kelongsoran. Penelitian ini bertujuan menganalisis efektivitas Bamboo Crib Wall sebagai alternatif perkuatan ramah lingkungan dan ekonomis dengan membandingkan desain tunggal (single-trap) dan bertingkat (multi-trap). Analisis stabilitas dilakukan menggunakan Metode Kesetimbangan Batas pada lereng setinggi 14 meter dengan sudut kemiringan 60° di Desa Tambakmerang, Wonogiri. Hasil simulasi menunjukkan bahwa lereng eksisting memiliki Faktor Keamanan (FK) sebesar 1,366. Kondisi ini dikategorikan relatif stabil namun belum memenuhi standar SNI 8460:2017 untuk lereng permanen dengan tingkat ketidakpastian tinggi yang mensyaratkan FK ≥ 2,0. Penerapan Bamboo Crib Wall desain single-trap (H = 4 m, B = 3 m) meningkatkan FK menjadi 1,571, tetapi masih di bawah persyaratan minimum standar nasional. Sementara itu, variasi desain bertingkat (2-trap) menghasilkan stabilitas paling optimal dengan nilai FK sebesar 2,823, yang telah jauh melampaui batas aman minimum. Penelitian ini menyimpulkan bahwa modifikasi Bamboo Crib Wall model bertingkat adalah solusi paling efektif karena sistem terasering memberikan distribusi beban dan retensi yang lebih baik dibandingkan model tunggal dalam menahan gaya penggerak pada lereng curam.